Estimation of turbulent boundary layer induced noise using energy flow analysis for ship hull designs. (February 2020) - Choi, Woen-Sug; Hong, Suk-Yoon; Kwon, Hyun-Wung; Seo, Jeong-Hwa; Rhee, Shin-Hyung; Song, Jee-Hun
A turbulent boundary layer develops on the surface of submerged bodies in motion; these layers consist of complex flows and interact with the structure causing turbulent boundary layer induced noise due to fluid-structure interaction. Recently, although the research on such noise has attracted great interest in the naval fields, owing to the focus on the competitive development of low-noise naval ships, the limitations corresponding to the application of methods developed in aeroacoustics for underwater structures having lower convection speed of turbulence and faster sound speed along with insufficient environments to conduct experiments restrained to subjects of simple structures at high frequency. To overcome the abovementioned limitations and study the noise characteristics for ship hull design, in this research, methods to analyze the noise radiated due to turbulent flow on the complex underwater structure are developed using energy flow analysis methods for vibro-acoustic calculations. For estimation of the input hydrodynamic forces, wall pressure fluctuation spectrum on the surface is obtained from turbulent boundary layer properties to acquire sufficient resolutions. The vibrational response of the structure is calculated using energy flow analysis incorporating the finite element method for structural forces estimated as input power. The acoustical response coupled with the vibrational response is obtained using the calculated vibrational energy density with the boundary element method in combination with the energy flow analysis, taking advantages of the fact that the methods share the common energy variables. Developed methods are validated with a case of broadband noise radiated from a plate. Using the procedures, numerical estimation and analysis of acoustic performance are performed for trimaran ship hull designs with steady-state computational fluid dynamics to demonstrate the method's usability as an assessment tool in the early design stage.